Sustainability Perceptions and Practices in Port Operations: A Qualitative Study Among Transportation Professionals - Tampubolon, Brenhard Mangatur; Herawati, Susi; Sibarani, Mauritz Halomoan Manontang (Jurnal Abdidas, 2024)
This qualitative study investigates sustainability perceptions and practices among transportation professionals in port operations. Through semi-structured interviews and analysis of international standards, key themes emerge regarding the importance of pollution reduction, adoption of green technologies, and challenges in implementation. Findings reveal a gap between awareness and action, highlighting the need for targeted interventions and capacity-building initiatives. Professionalism emerges as a critical factor in driving sustainability initiatives, underscoring the importance of training and knowledge-sharing platforms. Overall, the study contributes to the discourse on sustainability in transportation management and port operations, informing policy-making and strategic interventions aimed at fostering a culture of sustainability within the industry.